STUDI MORFOMETRIK UDANG BERAS MERAH (Metapenaeopsis palmensis) YANG TERTANGKAP PADA MALAM HARI DI PERAIRAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Firma Dhani; Muhammad R. Syahrir; Abdunnur Abdunnur (Jurnal Tropical Aquatic Sciences, 2022)
Southern Velvet Shrimp (Metapenaeopsis palmensis) of the Penaeidae family, morphometric measurements were carried out to see things that affect the shape of the species. This study was aimed to provide information about the morphometric study of red rice shrimp (Metapenaeopsis palmensis) caught at night in Samboja waters, Kutai Kartanegara. This research was conducted in October-November 2021, the sample used was 300 brown rice shrimp (Metapenaeopsis palmensis). The morphometric study used covariance analysis to look at 20 morphometric covariates that affect the total length (PTO). Based on the results of univariate anova test analysis, it is known that 20 morphometrics have a sig <0.05, which means that H1 is accepted, which means it has an effect on PTO. Furthermore, ancova analysis was carried out, 13 morphometric results were obtained which had sig <0.05 for PTO, namely rostrum length (RST), head length (PK), first segment length (PRP), second segment length (PRD), third segment length ( PRT), fourth segment length (PRE), fifth segment length (PRL), sixth segment length (PRN), headless length (PTK), telson length (TLN), carapace button length (PKB), third lower segment length (PTB) ), and the length of the fifth lower segment (PLB).